Natural cross-linker-stabilized acellular porcine corneal stroma for lamellar keratoplasty. (15th September 2020) - Li, Hua; Zhao, Long; Wang, Fuyan; Wang, Hongwei; Dong, Muchen; Liu, Ting; Ruan, Ting; Zhou, Mingming; Zhou, Qingjun; Xie, Lixin
Abstract: Acellular porcine corneal stroma (APCS) is a promising alternative to human donor cornea for lamellar keratoplasty (LKP). However, the detergents, enzymes and physical forces used during decellularization unavoidably alter the cornea's extracellular matrix composition and disrupt its ultrastructure, making it less mechanically stable and liable to degradation both in vitro and in vivo . Herein, we systematically analyzed the low biomechanics and easy degradability of APCS in terms of structure and protein composition. Then, we introduced natural cross-linkers, namely proanthocyanidin (PA), epigallocatechin-3-gallate and genipin, to stabilize the APCS that exhibited color variations during crosslinking. Then, we developed a protective crosslinking system by combining cross-linkers with bovine serum albumin (BSA) to reduce color change, maintain transparency and improve the mechanical property of APCS. PA/BSA-crosslinked APCS (PA/BSA-APCS) shows favorable corneal transparency and swelling property; the improved overall and surface corneal biomechanics were comparable to those of human cornea, revealing strong resistance to enzymatic degradation and good biocompatibility. Results from LKP in the rabbit model showed complete re-epithelialization without graft melting, the stitches were scarcely loosened after the operation and more host keratocytes had migrated in PA/BSA-APCS at six months post-operation. Therefore, PA/BSA-APCS could be useful as a corneal substitute for tissue regeneration and the protective crosslinking system could be applicable in other bioengineering fields. Graphical abstract: Image, graphical abstract